Sweden : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This Selected Issues paper on Sweden examines developments in the government structural balance. The paper identifies the respective contributions of cyclical and structural factors in the present fiscal consolidation phase. It reviews recent developments and the medium-term fiscal outlook. The paper presents estimates of the structural and cyclical components of the government financial balance. The factors responsible for the fiscal improvement anticipated over the medium term are analyzed. The paper also analyzes the medium-term outlook for public debt, with particular attention to the sensitivity of debt dynamics to different macroeconomic conditions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet